2021
DOI: 10.1002/pep2.24217
|View full text |Cite
|
Sign up to set email alerts
|

Stapled ACE2 peptidomimetics designed to target the SARS‐CoV‐2 spike protein do not prevent virus internalization

Abstract: COVID‐19 is caused by a novel coronavirus called severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). Virus cell entry is mediated through a protein‐protein interaction (PPI) between the SARS‐CoV‐2 spike protein and angiotensin‐converting enzyme 2 (ACE2). A series of stapled peptide ACE2 peptidomimetics based on the ACE2 interaction motif were designed to bind the coronavirus S‐protein RBD and inhibit binding to the human ACE2 receptor. The peptidomimetics were assessed for antiviral activity in an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 30 publications
6
48
0
Order By: Relevance
“…However, the last study pointed out that mono-stapled peptides can successfully constrained α-helical structure in solution but do not prevent virus internalization. Thus, according to the suggestion by Morgan et al, 42 the double stapling is a viable approach for inducing α1-helicity, which may prevent virus internalization as described by Curreli et al. 40 when smaller peptides (∼30 mer) are evaluated.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the last study pointed out that mono-stapled peptides can successfully constrained α-helical structure in solution but do not prevent virus internalization. Thus, according to the suggestion by Morgan et al, 42 the double stapling is a viable approach for inducing α1-helicity, which may prevent virus internalization as described by Curreli et al. 40 when smaller peptides (∼30 mer) are evaluated.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 41 Their lead peptide presented increased affinity for the RBD (IC 50 : 3.6 μM, K D : 2.1 μM) compared with the control group; a 35-mer sequence extracted from the hACE2. In contrast, Morgan et al reported that their 23-mer mono-stapled peptides effectively constrained the helical structure in solution, but none of those peptides prevented virus internalization, 42 which indicates that must be an optimal peptide length and number/position of the staples to reach antiviral activity. Moreover, these results agree and validate our theory that using stapled peptides derived from the α1 helix of hACE2 could lay the foundations for further optimization of a potential clinical candidate.…”
Section: Introductionmentioning
confidence: 95%
“…The crystal structure S-RBD/ACE2 complex solution triggered the drug-discovery efforts to discover entry inhibitors, including peptide analogs, monoclonal antibodies, and protein chimeras (38)(39)(40)(41)(42)(43)(44)(45)(46). Despite these new technologies and macromolecules as therapeutic agents, small molecules remain the preferred choice for drug development due to their better pharmacokinetic profile, stability, and dosage logistics (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, an argument can be made that the lack of binding here may be due to limited secondary structure in solution of the linear native peptide designed by Zhang et al [113]. Nonetheless, a different group has shown that even with stapling that dramatically improved helicity of their peptides, no appreciable binding activity was observed for either stabilized and non-stabilized peptides [123]. In our lab we have found that peptides rationally designed from the binding motifs of either ACE2 or S1 RBD display modest inhibitory activity in the low micromolar range (unpublished).…”
Section: S1 and S2 Targeted Peptidesmentioning
confidence: 95%